Effect on Compressive Strength of Concrete on Partial Replacement of Cement by Marble Dust and Fly Ash - Thakur, Naveen; Mahla, Rahul; Maharshi, Divyam; Karwasra, Rahul (International Journal of Computer Sciences and Engineering, 2022)
In this growing world of science and technology, the pollution is still a major problem across the globe, and construction industries play a vital role in air pollution and soil pollution. The use of marble stone in houses is on huge demand and because of this stone cutting and dressing, factories produces the dust in large quantity, which results in accordance of many problems when left freely in environment. So, keeping these problems in view, the reuse or recycle of this dust can help us in many ways. Hence, we used the marble dust as a cementitious material, by partially replacing cement in concrete, can help in reuse by large quantity. Also, the use of fly ash with cement in concrete was taken. The testing cubesof grade M10 were tested on accountability of marble dust and fly ash. The compressive strength of cubes was tested at duration of 7th days. The positive and negative behavior of concrete with duration was noticed. The production of cubes is economic and environmental.